Comparative Analysis of Late-Payment Tax Sanctions and Their Impact on Effective Tax Rates in Indonesia, Malaysia, and South Korea - Nur Faiza Hidayatul Khasanah; Ayudya Meizzaluna; Intan Dwi Lestari; Nafa Agustin Ningtias; Felizha Rachel Agistavianica; Putri Kameliya Ramadhani; Rena Dwi Novitasari (Journal of Strategic Behaviour Accounting, 2025)
This study examines the impact of late-payment penalties and interest charges on the effective tax rate (ETR) of corporations, using ShopNexa Company as a standardized simulation case across three jurisdictions: Indonesia, Malaysia, and South Korea. Late-payment penalties are often imposed as a percentage of the unpaid tax, while interest charges accrue daily or monthly until settlement. Although these sanctions serve as compliance enforcement tools, they also increase the total tax burden borne by firms, thereby altering their effective tax rate. The analysis employs a quantitative simulation approach with identical financial structures and applies statutory penalty and interest rules from each jurisdiction. The results indicate that both penalties and interest substantially elevate the ETR. Indonesia demonstrates a 5%–7% increase in ETR due to cumulative fines and interest, while Malaysia’s moderate penalty regime produces a smaller increase of around 3%. South Korea’s compounding interest mechanism results in the largest ETR escalation, up to 9%. The study highlights the importance of timely tax compliance and transparent enforcement to avoid excessive effective tax burdens. The findings offer policy insights for tax administrations to balance deterrence and fairness in penalty design.